Sword & planet - Ruocchio, Christopher; Akers, Tim, 1972-; Matthews, Susan R.; Butler, D. J. (David John), 1973-; Hachmeister, L. J.; Nye, Jody Lynn, 1957-; Cluess, Jessica; Green, Simon R., 1955-; Virdi, R. R.; Martezi, Anthony; Fehervari, Peter (Baen, 2021)
"Science fiction? Fantasy? Is it too much to ask for both? The distant future-like the distant past-is a place of myths, of legends, and of great heroes. Cyborg knights battle extraterrestrial demons to rescue a peaceful village. A young girl unlocks an ancient power to protect her world from offworld colonists. Here are stories not where magic is science, but with magic and science. Not knights and castles, but knights and starships. Wizards and ray guns. Swords and planets. In D.J. Butler's "Power and Prestige," a pair of two-bit mercenaries are hired to solve a murder in a labyrinth beneath a crumbling city at the end of time. A young knight must face down an alien menace and awaken the power within in R.R. Virdi's "A Knight Luminary," and in "Saving the Emperor" Simon R. Green takes us deep into the Imperial City of Virimonde . . . and offers a glimpse at how the Deathstalker clan rose to power and fame. Plus tales from Tim Akers, Jessica Cluess, L.J. Hachmeister, Susan R. Matthews, T.C. McCarthy, Jody Lynn Nye, Tom Toner . . . plus a new world from Warhammer 40,000 author Peter Fehervari, and a new chapter in the Sun Eater saga from Christopher Ruocchio. Contributors: Tim Akers, D.J. Butler, Jessica Cluess, Peter Fehervari, Simon R. Green, L.J. Hachmeister, Susan R. Matthews, T.C. McCarthy, Jody Lynn Nye, Christopher Ruocchio, Tom Toner, and R.R. Virdi"--